Trust in Danish journalists and news media: in decay or not? - Andersen, Kim; van Dalen, Arjen; Hopmann, David Nicolas; Skovsgaard, Morten; Albæk, Erik (Politica, 2021)
In this article, we examine 1) how trust in Danish journalists and news media has developed over time, 2) whether trust in different types of news media differs, and 3) how people’s party preference affect their trust in journalists and news media. Our analyses are based on comprehensive data from the European Commission, the Reuters Institute for the Study of Journalism, Radius Kommunikation, and DR Media Research, and show 1) that trust in journalists and news media is stable over time, 2) that people have higher trust in public service news and quality newspapers and lower trust in tabloid news media, and 3) that party preference explains some variations in trust.